БНХАУ-ын ӨМӨЗО-ы аж үйлдвэрийн хөгжлийн талаар товч өгүүлэх нь (Journal of International Studies, 2003)
English title: Briefly about industrial development of Inner Mongolian Autonomous territory of the PRC